Adoption Factor Of Mobile Marketing: The Case Of Small Medium Enterprises In Malaysia - Musa, Haslinda; Shirly, Chung Hsian Li; Zuraida, Abal Abas; Norhidayah, Mohamad (Econjournals, 2016)
In this era of globalization where information technology has taken place for fulfilling customer demands, small and medium enterprises (SMEs) have to fight in this intense competition in order to be able to gain their own market shares. To achieve targeted market shares, the use of mobile marketing as a medium for advertisement has evolved to an important tools for SMEs. Therefore, the main purpose of this study is to examine the factors that positively contribute to the adoption level of mobile marketing among Malaysian SMEs. From overall, 150 sample of questionnaire has collected from the SMEs all over Malaysia and analysed uses descriptive method. The result found that there is a positive relationship between branding strategy and technical knowledge towards the adoption level of mobile marketing.